Managers of complex change? How United Nations treaty secretariats jointly govern institutional interplay in global environmental governance - Joshua Philipp Elsässer (Environmental Policy and Governance, 2024)
Research on international bureaucracies, such as treaty secretariats, has predominantly focused on broadening our understanding of their role, function, and influence within their respective regulatory domains. However, the potential for treaty secretariats to manage situations of institutional overlap by coordinating with other agencies across policy areas has remained understudied. This article offers new empirical and theoretical insights for studying collective agency and coordination mechanisms in instances of institutional interaction within hybrid regime complexes. Specifically, it investigates how the treaty secretariats of the Rio Conventions under the United Nations employ joint interplay management as a means to improve institutional coherence within the climate change, biodiversity loss, and desertification nexus. Collectively, the public agencies aim to advance knowledge and discourse, influence norm-building processes and regulation, or build capacity and support the joint implementation of policy objectives addressing the interlinked environmental problems. They do this by interacting with various actors across governance levels, including national governments, transnational initiatives, private actors, or civil society. By tracing the process linking joint activities with effects of such interactions, this qualitative case study makes a conceptual contribution~by extrapolating a mechanistic theory for joint interplay management. The article demonstrates that treaty secretariats have to contend with challenges of resource allocation, diverging mandates, leadership priorities, and the degree of politicization and timing which frequently intervene stages of strategizing and executing joint activities. The results highlight that joint interplay management can be most impactful when secretariats employ orchestration practices through joint outreach and advocacy to advance coherent institutional responses to interdependent environmental problems.
Keywords: 330; coherence; global environmental governance; institutional interplay; institutional overlap; joint interplay management; treaty secretariats